Perlindungan dan Penyelesaian Hukum terhadap Investasi Asing di Indonesia - Ahmad, Agil; Purwanda, Sunardi; Suardi, Suardi; Ambarwati, Auliah; Tijjang, Bakhtiar; Fatimah, Dian; Yunus, Asrial (Primagraha Law Review, 2024)
Investment is the allocation of capital or resources with the aim of gaining profits in the future. Foreign investment is often considered the primary driver of economic development as it can increase the amount of capital available for development, create jobs, and introduce new technologies and management skills. In Indonesia, investment activities are regulated under Law Number 25 of 2007 concerning Investment and Law Number 6 of 2023 concerning Job Creation, widely known as the Omnibus Law, which also regulates investment. Despite having various regulations, the protection mechanisms are often debated, especially when conflicts arise between foreign investors and the government or local parties. Therefore, it is important to study how legal protection and dispute resolution related to foreign investment in Indonesia are addressed. The research method used in this study is normative with a comparative, legislative, and analytical approach. The types of data used in this research are primary and secondary data, where primary data consist of legislation, while secondary data consist of published documents that are not in official form, including legal textbooks, legal journals, legal papers, and so forth. The data analysis technique is qualitative and presented descriptively by explaining, describing, and illustrating issues closely related to the topic, then drawing conclusions based on analysis using deductive logic in line with prescriptive discipline. The results of the study show that both Law Number 6 of 2023 and Law Number 25 of 2007 provide legal protection to foreign investors, although the focus and approach used to provide such protection differ.